Prevalence and Antimicrobial Susceptibility Pattern of Urine Culture Isolates from a Tertiary Care Hospital, Dhaka, Bangladesh - Sharmin, Sanzida; Huda, Md. Nazmul; Afroz, Jinia (European Journal of Applied Sciences, 2022)
Urinary tract infections are known as the most common bacterial infections, affecting a significant number of people every year. The study was designed to highlight the common bacterial pathogens causing urinary tract infections and to determine antimicrobial susceptibility patterns of the most frequent urine culture isolates. From the total of 436 samples, 183 isolates were found. Among all isolates, E. coli was the most predominant (40%) urinary tract infection pathogens followed by Enterococcus sp. (23%), Staphylococcus sp.( 15%), Klebsiella sp.( 13%), Proteus sp.( 5%), Pseudomonas sp.( 2%) and Acinetobacter sp (2%). Rate of isolation was higher in female patients (76%) rather than male (24%). Out of all 76% isolates from females, highest (36.69%) rate of isolation among females of 21-40 years age group followed by 41-60 years age group (33.81%). In the case of male, the rate of isolation was more in the age group of 41-60 years (38.64%). E. coli showed a remarkable amount of sensitivity against Amikacin (95%), followed by Nitrofurantoin (89%) , Imipenem (77%) and Meropenem (70%) respectively. Now a days, complicated urinary tract infections and antimicrobial resistance pose a major threat in the treatment of this type of infection. It is therefore suggested that the problem of antimicrobial resistance can be reduced through appropriate use of antimicrobial agents and increasing awareness among the population.